2023
DOI: 10.1021/acs.jmedchem.3c00061
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of Cannabidiol-Based Analogs as Negative Allosteric Modulators of the μ-Opioid Receptor

Taryn Bosquez-Berger,
Jessica A. Gudorf,
Charles P. Kuntz
et al.

Abstract: The US faces an unprecedented surge in fatal drug overdoses. Naloxone, the only antidote for opiate overdose, competes at the mu opioid receptor (μOR) orthosteric site. Naloxone struggles against fentanyl-class synthetic opioids that now cause ∼80% of deaths. Negative allosteric modulators (NAMs) targeting secondary sites may noncompetitively downregulate μOR activation. (−)-Cannabidiol ((−)-CBD) is a candidate μOR NAM. To explore its therapeutic potential, we evaluated the structure–activity relationships amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Some flavonoid subgroups have been ignored by the organocatalytic community, such as pterocarpans [61] . Also, the recent discoveries that cannabidiol ( 53 ) analogs can interact with μ‐opioid receptors [62] and have the potential to treat morphine induced addictions [63] are proof that new enantioselective synthetic methodologies capable to provide structural diversity around the cannabinoid‐core (hexahydro‐6 H ‐benzo[ c ]chromene) ( B ) are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Some flavonoid subgroups have been ignored by the organocatalytic community, such as pterocarpans [61] . Also, the recent discoveries that cannabidiol ( 53 ) analogs can interact with μ‐opioid receptors [62] and have the potential to treat morphine induced addictions [63] are proof that new enantioselective synthetic methodologies capable to provide structural diversity around the cannabinoid‐core (hexahydro‐6 H ‐benzo[ c ]chromene) ( B ) are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…The main effect of CB1 and CB2 receptor antagonism is to reduce the binding capacity of tetrahydrocannabinol (THC) and its related isomers [13]. T. Bosquez-Berger et al [14] also studied its ability to exhibit partially antagonistic properties to serotonin receptors. Cannabidiol is also an allosteric opioid receptor modulator.…”
Section: Analysis Of Chemical Pharmacodynamic and Pharmacokinetic Fea...mentioning
confidence: 99%
“…In fact, CBD was long ago identified as an agonist of the 5-HT 1A R (with low potency, in the micromolar range) [14]. Recently, Bosquez-Berger et al have convincingly shown that CBD is an allosteric modulator of the µ-opioid receptor [15]. A list of potential receptor targets of CBD was provided in a 2015 review paper in which the A 2A R was not included [16].…”
Section: Introductionmentioning
confidence: 99%